비유를 활용한 STEAM 프로그램 개발 및 효과 : 중학교 '태양계' 단원을 중심으로 - 한신; 김형범; 김용기; 송하명; Han, Shin; Kim, Hyoungbum; Kim, Yong-Ki; Song, Ha-Myung (대한지구과학교육학회지, 2020)
This study aimed to develop an HTE (It is an abbreviation for Here, There, and Everywhere) STEAM program combining with the use of an analogy in a middle school subject unit 'the solar system' and realize creative education for intelligent information society through a process of verifying the effectiveness of the program. For reference, the program was applied to 354 students in the first grade of two middle schools in South Korea - one was A middle school in Sejong City, the other B middle school in Pyeongtaek City. The STEAM program was revised and made up for the weak points for three times by a group of experts, and then it got verified for validity. The final version of the program was applied to middle school education sites in Korea for six periods in total. In other to confirm the effectiveness, two types of tests - logical thinking ability test and STEAM attitude test - were conducted before and after the program treatment. On top of that, the STEAM satisfaction test was also implemented in order to explore the students' recognition of the program after the program treatment. The results of this study were as follows. First, it turned out the STEAM program using the analogy was effective in improving the students' logical thinking ability. Second, the STEAM program blended with the analogy was also effective in improving the students' STEAM attitude. Third, the students' recognition of the STEAM program using the analogy was quite positive, and the program was efficacious in intriguing the students' interests in science. Judging from the results of the program, the students' satisfaction with the classes they take will be expected to be higher if the STEAM program is implemented in the next-term classes with more sufficient time. 이 연구의 목적은 중학교 '태양계 단원에서 비유를 활용한 HTE(Here, There, Everywhere) STEAM 프로그램을 개발하고, 이 프로그램을 세종시 소재 A중학교와 평택시 소재 B중학교의 1학년 중학생 354명에게 적용하여 프로그램의 효과성을 검증하는 과정을 통해 지능정보사회를 대비한 창의교육을 실현하는데 있다. 개발한 STEAM 프로그램은 전문가 집단을 구성하여 3차례에 걸쳐 수정, 보완하여 타당성을 검증받았으며, 최종 개발된 프로그램은 총 6차시에 걸쳐 현장에 적용하였다. 이에 따른 효과성을 알아보기 위해 논리적 사고력 검사와 STEAM 관련 태도 검사를 프로그램 처치 전과 처치 후에 실시하였으며, 프로그램에 대한 학생들의 인식을 알아보기 위해 프로그램 처치 후 STEAM 만족도 검사를 실시하였다. 이 연구의 결과는 다음과 같다. 첫째, 비유를 활용한 STEAM 프로그램이 중학생의 논리적 사고력 향상에 효과적인 것으로 나타났다. 둘째, 비유를 활용한 STEAM 프로그램이 중학생의 STEAM 태도 향상에 효과적이었다. 셋째, 비유를 활용한 STEAM 프로그램에 대한 중학생의 인식이 긍정적이며, 과학에 대한 흥미를 일으키는데 효과적이었다. 이러한 결과를 통해 차기 수업에서는 충분한 시간을 통해 STEAM 프로그램 수업을 수행한다면 중학생들의 수업에 대한 만족도가 더욱 높아질 것으로 사료된다.